Influence of a minimum wage on a labour market (Economic and Political Thought, 2014)
The issue of labour markets has been of interest not only to the theory ofeconomics but also the economic policy practice for years. The importance ofthis issue results mainly from a common phenomenon of unemployment and itseconomic and social dimensions. With the occurrence of rising unemploymentin the world, special attention was paid to institutional factors influencinglabour markets, such as a statutory minimum wage, labour-related tax, labourlaw regulations and a model of negotiating remuneration. Several yearsafter the introduction of the first minimum wage regulations, a call for raisinga minimum wage is still a popular topic of public debate in many countries. Participationin this debate, however, requires understanding of the dependenciesand the influence of a minimum wage on a labour market. The article aims topresent the dependencies and consequences of the use of a minimum wage.The successive parts of the article present facts and data regarding a minimumwage in particular countries, a theoretical description of a minimum wage andan analysis of the influence of a minimum wage on a labour market. The examinationof the influence of a minimum wage on a labour market is conductedfrom the point of view of the influence of this instrument based on the size ofa labour market, i.e. the level of employment and unemployment as well as thedifferentiation of remuneration in the economy.